Monetary policy aspects of the enlargement of the Euro area - Kirsten Lommatzsch; Silke Tober (Deutsche Bank Research, 2002)
There is some evidence that interdependencies among European banks have increased over the past 15 years and that the potential of systemic risks in banking has shifted from a national level to a European level. / Whereas wholesale financial markets are considered to be highly integrated within the European Union, integration in retail financial markets is less advanced, as a study on measuring financial market integration including an analysis of obstacles to financial market integration shows.
Keywords: 330; Geldpolitik; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Zentralbank; Inflation; EU-Staaten; Osteuropa